Electromyography of the External Anal Sphincter during Micturition and Electrophysiological Bulbocavernosus Reflex in Healthy Spayed Female Canines - Nicha Mongkolrat; Areerath Akatvipat; Phitchaya Saenubol; Pachara Pornnimitara; Sukolrat Boonyayatra; Siam Tongprasert (Veterinary Medicine International)
This study aimed to find methods and interferences and illustrate the pattern of external anal sphincter (EAS) electromyography (EMG) during micturition and to determine reference intervals of electrophysiological bulbocavernosus reflex (EBCR) by using robust statistical methods in healthy spayed female canines. Ten healthy spayed female canines (no breed restriction) with a body weight of 11.3–18 kg were enrolled. EAS EMG during micturition and the EBCR test were performed under light general anesthesia. Altogether 25 out of 34 EAS EMG showed a similar pattern, including low-amplitude high-frequency bursting pattern before voiding, medium- or high-amplitude low-frequency bursting pattern at the beginning of voiding, oscillate medium- and/or high-amplitude low-frequency bursting with a low-amplitude high-frequency bursting pattern during voiding, and high-amplitude high-frequency bursting pattern at the end of voiding. An average of 100 consecutive stimulations of EBCR for one cycle were performed in each dog and another cycle was repeated to ensure reproducibility. The lower and upper limits of the reference interval of EBCR onset latency values and EBCR mean amplitude values were calculated using both standard and robust methods with untransformed and transformed Box-Cox data. The EBCR onset latency was between 13.85 and 27.44 milliseconds, whereas the EBCR mean baseline to peak amplitude was not transformed with Box-Cox transformation. All EBCR compound muscle action potentials started with a negative sharp wave, which tapers from the baseline in the upward direction, showing an upturned bell-shaped curve. In conclusion, this study was possibly the first to examine the method and provide the electrographic pattern of EAS EMG during micturition and reference intervals of EBCR onset latency in spayed female dogs, which may serve as baseline information to help veterinarians differentiate healthy from diseased dogs. Further studies should compare normal dogs and dogs with lower urinary tract abnormalities at different lesion locations.